Divergent perspectives about water security: hydrosocial transformations in the metropolitan region of Montevideo (Uruguay) - Dias Tadeu, Natalia; Trimble, Micaela; Lázaro, Marila; Venturini, Paula; Venegas, Mauricio (Frontiers in Sustainable Cities, 2023)
The Montevideo Metropolis, where more than half of Uruguay's population resides, is supplied with water from the Santa Lucía River (SLR), which faces increasing problems of water quality and quantity. In 2020, in the context of national government political changes, a hydraulic project (called Neptuno) involving the construction of a purification plant using water from the Río de la Plata estuary (close to the SLR basin), was proposed by a consortium of private companies. The aim of this paper is to analyze the arguments to support and oppose the Neptuno Project, as well as the hydrosocial transformations promoted by it in the SLR basin, including the scalar strategies adopted. Primary and secondary data (interviews, participant observation, and document analysis) were triangulated. Coalitions pro and against the greater involvement of the private sector with water supply services were identified. Our research shows that diverse perspectives of water security, related to different hydrosocial projects, reflect opposed interests and divergent objectives in a context of disputes within asymmetrical power relationships. This has been reactivating the coalition of the historic conflict against the privatization processes that preceded the constitutional reform in Uruguay in 2004. This coalition, against the Neptuno project, carried out a “jump scale,” taking the issue from the local to the national scale.